การสังเคราะห์งานวิจัยเกี่ยวกับรูปแบบการเรียนการสอนที่ส่งผลต่อผลสัมฤทธิ์ทางการเรียน วิชาภาษาอังกฤษโดยการวิเคราะห์อภิมาน - Phromprasri, Nattaya; Klangprapan , Marasri; Palajit, Somkiat (Journal of Graduate School Sakon Nakhon Rajabhat University, 2022)
The purposes of this research were to 1) analyze the features of the research studies, and 2) compare the difference in the effect size of the research studies on instructional models affecting the English learning achievement. The subjects in this research were 128 postgraduate theses conducted in public universities in Thailand and published from 2000 to 2018 on the ThaiLIS database. The research instruments consisted of 1) a research quality evaluation form with the selected criteria for assessing the quality of research studies, 2) a form to record the features of the research studies, and a manual for encoding the research studies. To measure the research effect size, Glass’s formula was employed. The statistics for data analysis were percentage, mean, and standard deviation, and the difference comparison of the research effect size using a formula of the Kruskal-Wallis Test. The findings were as follows: 1. The research studies were mostly conducted in 2014. The majority of research studies were completed at Udon Thani Rajabhat University. Most research studies were created by the Curriculum and Instruction program. The majority of research studies were undertaken in lower secondary schools. Integration-focused instructional models were the most popular. The duration of the experiment was mostly set between 11 and 20 hours. Most samples were obtained by using probability and adopted the One Group Pretest-Posttest Design. The lesson plans were mostly employed as the research instruments and their validity, reliability, difficulty, and discrimination were all evaluated. The most commonly utilized basic statistics were mean and standard deviation. The most common method of testing the hypothesis was the t-test. 2. The comparative analysis of the differences in the effect size of the instructional model’s effect on English achievement by using the Kruskal-Wallis test revealed that 2.1 The effect size of the instructional models showed differences at the .05 level of significance. 2.2 The level of the sample group and the effect sizes of the instructional models affecting English achievements showed no differences.